Multicentre study to evaluate the clinical effects of laparoscopic uterine artery occlusion in combination with myomectomy to treat symptomatic uterine leiomyomas. (September 2016) - Yang, W.; Cheng, Z.; Yu, J.; Yang, H.; Liu, Z.; Ren, Q.; Xu, L.
Abstract: Objective: Uterine artery occlusion is often used to treat symptomatic uterine myomas, as this is a minimally invasive approach. However, alternative methods for uterus-sparing therapy are in development. This study aimed to compare the clinical effects of laparoscopic uterine artery occlusion (LUAO) in combination with laparoscopic myomectomy (LM) with LM alone for the management of symptomatic uterine leiomyomas. Study design: This multicentre study was a retrospective controlled investigation. In total, 618 patients with symptomatic uterine myomas from six hospitals in Eastern China underwent LUAO + LM or LM alone between June 2011 and December 2012. Operative time, blood loss, transfusion, highest temperature, postoperative hospital stay, complications and follow-up results were compared between the two groups. Results: Complete clinical data were available for 504 patients. Among these, 324 patients underwent LUAO + LM and 180 patients underwent LM alone. Mean ± standard deviation blood loss, transfusion, highest peri-operative temperature and duration of hospital stay were significantly lower in the LUAO + LM group compared with the LM group (83.61 ± 53.70 ml vs 109 ± 58.43 ml, 1.85% vs 6.11%, 37.6 ± 0.40 °C vs 37.9 ± 0.45°C and 5.11 ± 0.62 days vs 6.10 ± 0.83 days, respectively). The mean duration of follow-up was 38.97 ± 5.82 months in the LUAO + LM group and 37.30 ± 2.25 months in the LM group ( p > 0.05). The relief of abnormal uterine bleeding, reduction of uterine volume and recurrence of myomas were more remarkable in the LUAO + LM group than the LM group (97.22% vs 83.75%, 62.42% vs 51.83% and 3.47% vs 10.63%, respectively). Conclusions: LUAO in combination with LM was associated with higher surgical quality, greater relief of abnormal symptoms and less recurrence of myomas compared with LM alone. LUAO in combination with LM is recommended for women with symptomatic uterine myomas who wish to preserve their uterus.